β-thalassemia mutations in Jamaica: geographic variation in small communities - Serjeant, Graham R.; Serjeant, Beryl E.; Mason, Karlene P.; Happich, Margit; Kulozik, Andreas (Hemoglobin, 2018)
Over the last 43 years, surveys of over 200,000 subjects in Jamaica have identified β-thalassemia (β-thal) mutations. In most, these genes were detected at birth in patients with sickle cell-β-thal and so the prevalence and distribution would not be influenced by subsequent clinical course. There were two newborn populations, 100,000 deliveries in the corporate area between 1973-1981 and 84,940 in south and western Jamaica between 2008-2016. A third population, which derived from the Manchester Project in central Jamaica, screened 16,612 secondary school children, aged predominantly 15-19 years, and identified 150 students with the β-thal trait and 11 with sickle cell [Hb S (HBB: c.20A>T)]- or Hb C (HBB: c.19G>A)-β-thal. The latter patients may have been subject to symptomatic selection, but this should not have affected those with β-thal trait. Of the 24 different molecular mutations, β0-thal genes accounted for 10.0-27.0% of these groups and most common was IVS-II-849 (A>G) (HBB: c.316-2A>G). Of the β+ mutations, seven subjects had severe genes with low levels of β chain synthesis but the majority were benign mutations in the promoter region. The -29 (A>G) (HBB: c.-79A>G) mutation dominated in the newborn study in Kingston, similar to experiences in Guadeloupe and African Americans but the -88 (C>T) (HBB: c.-138C>T) mutation was more common among school students in central Jamaica. Caribbean populations are genetically heterogeneous but variations within different parts of Jamaica is of potential importance for prenatal diagnosis and genetic counseling. This information may also be useful among the large Jamaican diaspora.
Published online: 09 Jan 2019
Gesehen am 30.09.2019